Physical and psychological motivation tests of individual preferences in rainbow trout. (4th February 2017) - Maia, C. M.; Ferguson, B.; Volpato, G. L.; Braithwaite, V. A.
Abstract: Animal preference and motivation have been used to assess different kinds of environmental resources that may help improve welfare conditions. However, preference and motivation are typically tested separately, and these assays disregard the individual nature of responses. Here, in rainbow trout ( Oncorhynchus mykiss ), we evaluated individual variability of preference for different resources, and whether these fish are motivated to access such preferred options. Individual fish were allowed to sample among four different compartments. Two different tests were used, one where the compartments varied in background colour, the other where the compartments varied in what they contained. Over a series of 10 days, the fish interacted with these different options and during the trials of the last 7 days, their visitation frequency to each compartment was registered every 30 s. The data were used to calculate a preference index for each fish. Physical motivation of individual fish to access preferred and dispreferred options was then tested by quantifying the frequency of pushes the fish gave to transparent hinged doors that led to the different compartments. In a separate test, whether fish entered a preferred or a dispreferred option after crossing an aversive open and brightly lit, along area was used as a measure of psychological motivation. Trout showed a strong preference for blue backgrounds, and were both more physically and psychologically motivated to access this color. However, preference and motivation for alternative items such as shelters or conspecifics were more variable. We conclude that the physical and psychological motivation of trout depend on the resources that they are trying to access, but the fish express stronger motivation to gain access to more preferred options. Abstract : To give animals an enriched environment, it is important to assess what they prefer. Preference can be measured by contrasting preferred choices with the effort an animal makes to access these items (motivation). Using Maia and Volpato (2016)'s preference index, we demonstrated that rainbow trout express both physical and psychological motivation to access their preferred background colour, or to access shelters or conspecifics.